DEVELOPMENT, VALIDATION AND KINETIC APPLICATION OFSPECTROMETRIC METHODS FOR THE ANALYSIS OF ASPIRIN, SALICYLICACID, AND CAFFEINE AS SINGLE-COMPONENT AND IN MIXTURES - Aqeela Khurshid et al (Baqai Journal of Health Sciences)
Aspirin (ASA) and aspirin-caffeine dosage forms are widely used as analgesic drugs. In the present study specific stability-indicating two- and three-component spectrometric methods have been developed for the assay of ASA and its degradation product, salicylic acid, in the presence and absence of caffeine (CF). The methods have been validated with respect to different parameters such as linearity, range, accuracy, precision, reproducibility, limit of detection, limit of quantification and specificity. The results indicated that the proposed methods are linear in the range of 0.00050.005 mg%, highly accurate (99.0100.1%), precise (<3.0% RSD) and robust (<2.0% RSD). These methods have been applied for the assay of ASA in its thermally degraded solution and in degraded tablets. The apparent first-order rate constants (kobs) for the degradation of ASA at pH 8.010.0 in the absence and presence of CF are in the range of 5.3711.0×103 min1 and 4.9910.30×103 min1, respectively. The accuracy and specificity of the methods have been confirmed from the linearity of first-order plots around the assay data for the degradation of ASA. These methods can accurately determine ASA in the presence of interfering substances.